RETRACTED: Learning Model Development for Vocational Education Based on Industry Work Culture - Widarto Widarto (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Teknologi dan Kejuruan entitled “Learning Model Development for Vocational Education Based on Industry Work Culture” Vol 25, No 2, pp. 213-218, October 2019DOI: 10.21831/jptk.v25i2.27227 This paper violates the Jurnal Pendidikan Teknologi dan Kejuruan Publication principles and has been retracted. The editor investigated and found that the paper has been published in the Journal of Physics: Conference Series Volume 1273. The document and its content have been removed from Jurnal Pendidikan Teknologi dan Kejuruan, and reasonable effort should be made to remove all references to this article.